Molecular Profiling and Antibiotic Resistance of Salmonella Enterica Subsp. Enterica Isolated from Indigenous Ulam and Poultry Meat - Lee, Learn Han (2007)
Salmonella enterica subsp. enterica formed the major group that represents nearly 60% of the salmonellae. Salmonella organisms emerged as a public health problem in many countries as salmonellosis has become the most prevalent foodborne disease worldwide. It has been estimated that approximately 1.4 million cases were reported annually in the developed nations such as USA. In Malaysia, of 8,640 cases of food poisoning reported by the Ministry of Health for the year 1999, 811 (9.4%) were due to Salmonella. The purpose of this study was to characterize and study Salmonella enterica subsp. enterica (S. enterica) using multiple antimicrobial resistance and several molecular typing methods including plasmid profiling, PCR-RFLP, RAPD, ERIC-PCR and Multiplex PCR on antibiotic resistant gene. The isolate were recovered from poultry meat (55), four types of indigenous vegetables namely ‘selom’ (Oenanthe stolonifera) (59), ‘pegaga’ (Centella asiatica) (20), ‘kesum’ (Polygonum minus) (41), ‘kangkong’ (Ipomoea aquatica) (14) and processed food (11).Genomic DNA of the 200 S. enterica isolates belonging to 43 different serovars were recovered from poultry meat, various indigenous vegetables and processed food was confirmed by specific and duplex PCR targeting the iroB gene that yielded 443 bp and 606 bp amplicons. The PCR amplification of iroB gene is a rapid and reliable method for distinguishing between S. enterica and other bacterial species. Plasmids of S. enterica varied in sizes from 2 to more than 200 kb. Despite limited knowledge on their function, their presence is frequently used for strain differentiation in epidemiological studies. Plasmid profiling on the 200 S. enterica isolates demonstrated high discriminatory capability for serovars differentiation in this study that was clustered into 70 groups based on the number and pattern of the bands. One of the amplification based techniques used in this study for molecular characterization was PCR-RFLP that incorporated PCR of iroB1, iroB2 and restriction digest with BglII and AluI to determine the relatedness of bacterial strains. Results obtained showed that PCR-RFLP has excellent typeablity but low discriminatory power due to its inability to produce different banding patterns. ERIC sequences are short, highly conserved 126 bp non-coding regions found in the Enterobacteriaceae. Its location in bacterial genomes allows discrimination at the genus, species and serovars levels. RAPD is an amplification-based technique using arbitrary primers to detect changes in the DNA sequence at the sites in the genome and enable the discrimination of samples according to sources and serovars. Dendrogram of RAPD and ERIC-PCR were analyzed and comparisons made using BioNumerics gel analysis software (Applied Maths, Kortrijk, Belgium). Among the 200 isolates of S. enterica, RAPD with arbitrary primers OPAR02, OPAR17 and OPAR19 generated 47 clusters and 13 single isolates whereas ERIC-PCR with primers ERIC-1 and ERIC-2 produced 46 clusters and 12 single isolates at 60% similarity level with discriminatory index (D) of 0.9726 and 0.9606 respectively. Composite analysis of RAPD and ERIC-PCR profiling simultaneously produced 50 clusters and 18 single isolates at 60% similarity level with highest discriminatory index of 0.9824. These results demonstrated that composite analysis of RAPD (OPAR02, OPAR17 and OPAR19) together with ERIC-PCR are a better tool for differentiation and characterization of S. enterica as compared to a single method approach. The multiplex PCR targeted three different antibiotic resistance genes that was used to detect TEM, PSE-1 and cmlA/tetR genes segment encoding resistance towards ampicillin, chloramphenicol and tetracycline, respectively which could reduce labour and cost in analysis of a large number of isolates. Subsequently antimicrobial resistance was performed using disc diffusion method with a selection of 13 different antimicrobial agents. Total of 66 profiles were generated and multiple antimicrobial resistance (MAR) analysis indicated poultry meat still remains as the main reservoir for multi drug resistant Salmonella. In contrast, six isolates from the indigenous vegetables showed the highest MAR index (0.69). This might be due to animal waste fertilizer, irrigation water, contaminated container and improper handling of food by human that contributed to be the sources of Salmonella contamination of vegetables. Further investigations need to be conducted to determine if Salmonella isolates in recovered from indigenous vegetables were gaining more antimicrobial resistance. The characterization of MAR enabled the determination of antimicrobial patterns and trends in Salmonella from poultry meat and indigenous vegetables in Malaysia. As a conclusion, the results from this study could provide valuable information on the epidemiology and drug resistance trends of S. enterica, and hence contribute towards better surveillance and infection control measures as well as improved public health policy.